Biogenic synthesis of selenium nanoparticles using Hibiscus esculentus L. extract: Catalytic degradation of organic dye and its anticancer, antibacterial and antifungal activities - Ebrahimzadeh, Mohammad Ali; Moradsomarein, Mina; Lalerdi, Fatemeh Sadeghi; Alizadeh, Seyedeh Roya (European Journal of Chemistry, 2023)
In this work, we develop the synthesis of selenium nanoparticles (B@SeNPs) using a green method using the aqueous extract of Hibiscus esculentus L. Various techniques were used to characterize bio-synthesized B@SeNPs. The mixture color was clearly changed to reddish at 45-50 °C and the extract pH = 6. According to Fourier transform infrared spectroscopy (FT-IR), the B@SeNPs were produced, capped, and stabilized using biomolecules found in plant extracts. The energy dispersive X-ray (EDX) analysis profile revealed an atomic Se signal (1.39 mV). The powder X-ray diffraction (PXRD) pattern confirmed the hexagonal phase crystalline form of B@SeNPs. The zeta potential for SeNPs was determined to be -51.3 mV. Scanning electron microscope (SEM) and transmission electron microscopy (TEM) micrographs revealed spherical Se particles with sizes of roughly 62 nm. Furthermore, B@SeNPs can degrade methylene blue dye by 98.3% at 21 min with a rate constant of 0.1023 min-1 in the presence of NaBH4. In biological evaluation, the synthesized nanoparticles have been proven to be effective against two human cancers (AGS and MCF-7 cells) with IC50 values of 20.46 and 88.43 µg/mL, respectively. Additionally, B@SeNPs showed high safety in the Beas cell line (normal) at 123 µg/mL as the highest concentration. The biofabricated SeNPs had a moderate antibacterial effect against ATCC and multidrug-resistant clinical isolates. They had no antifungal activity against the tested fungus strains except C. albicans (IFRC 1873), with a MIC value of 138.75 µg/mL. Finally, the green-synthesized B@SeNPs could be a contender for further testing as a chemotherapeutic agent in the treatment of some human cancers.